2010
DOI: 10.1080/19361610.2011.529414
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analyses of Installation Patterns and Characteristics of Residential Burglar Alarms

Abstract: The dearth of research on spatial analyses for installation patterns and characteristics of residential burglar alarms exists in the crime prevention literature in general, and even a few existing studies are based on observational and anthropological approaches with little quantitative analyses. Spatially analytical approaches have not been used to examine the distribution and pattern of burglar alarms. With installation record of burglar alarms, spatial statistical techniques are used to examine spatial patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Elderly people are well-known as an important informal guardianship in crime literature [53], which meant that an area with more people over the age of 60 was expected to have fewer residential burglaries. In this research, Over60 was found to be associated with residential burglaries negatively in most of the PSMAs, except for 12.…”
Section: Spatial Analyses Of the Coefficientsmentioning
confidence: 99%
“…Elderly people are well-known as an important informal guardianship in crime literature [53], which meant that an area with more people over the age of 60 was expected to have fewer residential burglaries. In this research, Over60 was found to be associated with residential burglaries negatively in most of the PSMAs, except for 12.…”
Section: Spatial Analyses Of the Coefficientsmentioning
confidence: 99%
“…In 1852, Augustus Pope, a Boston inventor, secured a patent for the first electric burglar alarm system that could also signal the fire department. Edwin Holmes of Boston purchased the patent in 1857 and pioneered the electronic security alarm business (Lee, 2011). He had a difficult time convincing people that an alarm would sound on the second floor of a home when a door or window was opened on the first floor.…”
Section: The History Of Loss Prevention In a Nutshellmentioning
confidence: 99%
“…In recent times cameras have been affixed to the residential armamentarium. A variety of alarm systems have contributed to the protection of people, commerce and industry, institutions, and government (Lee, 2010(Lee, , 2011(Lee, , 2021McCrie, 1988;McCrie & Lee, 2023). This study primarily focuses on burglar alarm systems and their spatial effects.…”
Section: Introductionmentioning
confidence: 99%